MODERN INTERPRETATION OF SURKHANDARYA ETHNIC COSTUME IN CONTEMPORARY FASHION DESIGN (Ideal Journal of Multidisciplinary Research, 2026)
This article presents an in-depth analysis of the transformation of traditional Surkhandarya national costume into contemporary fashion design within the framework of ethno-style and Pret-à-Porter de Luxe collections. The study explores the historical, cultural, aesthetic, and technological aspects of traditional garments and their adaptation to modern fashion requirements. Particular attention is given to the preservation of cultural identity, the application of traditional textiles such as adras and cotton, and the reinterpretation of ornamentation and decorative elements in modern design. The research also examines the role of ergonomic principles, material selection, and constructive solutions in enhancing the functionality and aesthetic appeal of contemporary clothing. The results demonstrate that the integration of national heritage into modern fashion not only contributes to the development of innovative designer collections but also promotes Uzbekistan’s cultural identity in the global fashion industry.
Keywords: Surkhandarya national costume, ethno-fashion, Pret-à-Porter de Luxe, Uzbek fashion, cultural heritage, textile design, traditional ornamentation, costume transformation, modern design, fashion innovation.